Endovascular pulmonary artery restenosis treatment after Tetralogy of Fallot surgical correction - Yu. L. Kuzmenko; A. V. Maksimenko; A. A. Dovgalyuk; M. P. Radchenko; O. O. Motrechko; N. M. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2017)
The most common complications in long-term period after Tetralogy of Fallot are: pulmonary artery restenosis (at the level of trunk, bifurcation or branches), ventricular septal defect reshunt, residual pulmonary artery stenosis (subvalvular, valvular) stenosis, RV-PA conduit stenosis, ventricular fibrillation, atrioventricular block, right ventricular aneurysm, infective endocarditis.Objective. Analisys of endovascular methods effectiveness for pulmonary artery residual stenosis or restenosis after ToF surgery.Materials and methods. From 2014 to 2016 28 patients after Tetralogy of Fallot surgery undergone endovascular interventions due to the pulmonary artery branches stenosis. Stenting of PA has been applied in all unfavorable cases for balloon dilatation.Conclusions. The most common complication after Tetralogy of Fallot surgery is a residual pulmonary artery stenosis. Endovascular techniques are effective and less traumatic alternative comparing to surgical treatment for residual pulmonary artery lesions.